Team‐based approach to identify cardiac toxicity in critically ill hematopoietic stem cell transplant recipients. Issue 10 (8th March 2017) - Dandoy, Christopher E.; Jodele, Sonata; Paff, Zachary; Hirsch, Russel; Ryan, Thomas D.; Jefferies, John L.; Cash, Michelle; Rotz, Seth; Pate, Abigail; Taylor, Michael D.; El‐Bietar, Javier; Myers, Kasiani C.; et al.
Abstract: Introduction: We observed pulmonary hypertension (PH), pericardial effusions, and left ventricular systolic dysfunction (LVSD) in multiple critically ill hematopoietic stem cell transplant (HSCT) recipients. We implemented routine structured echocardiography screening for HSCT recipients admitted to the pediatric intensive care unit (PICU) using a standardized multidisciplinary process. Methods: HSCT recipients admitted to the PICU with respiratory distress, hypoxia, shock, and complications related to transplant‐associated thrombotic microangiopathy were screened on admission and every 1–2 weeks thereafter. Echocardiography findings requiring intervention and/or further screening included elevated right ventricular pressure, LVSD, and moderate to large pericardial effusions. All echocardiograms were compared to the patient's routine pretransplant echocardiogram. Results: Seventy HSCT recipients required echocardiography screening over a 3‐year period. Echo abnormalities requiring intervention and/or further screening were found in 35 (50%) patients. Twenty‐four (34%) patients were noted to have elevated right ventricular pressure; 14 (20%) were at risk for PH, while 10 (14%) had PH. All patients with PH were treated with pulmonary vasodilators. LVSD was noted in 22 (31%) patients; 15/22 (68%) received inotropic support. Moderate to large pericardial effusions were present in nine (13%) patients, with six needing pericardial drain placement. Discussion: Echocardiographic abnormalities are common in critically ill HSCT recipients. Utilization of echocardiogram screening may allow for early detection and timely intervention for cardiac complications in this high‐risk cohort.